Water vapor transport and its influence on water stable isotopes in the Dongting Lake basin - X. Xiao; X. Zhang; X. Zhang; Z. Xiao; Z. Liu; D. Wang; C. Zhang; Z. Rao; X. He; X. He; H. Guan (Atmospheric Chemistry and Physics)
Understanding water vapor sources and transport paths is essential for assessing the water cycle and predicting precipitation accurately. Utilizing water vapor diagnosis and calculations, this study determined the water vapor sources and transport paths leading to precipitation in the Dongting Lake basin in four seasons (represented by January, April, June, and October). In January, the water-vapor-generating precipitation originated from the Arabian Peninsula, driven by the southern branch of the westerlies over the southern side of the Tibetan Plateau, along the northern side of the Indian Peninsula through southwestern China to reach the Dongting Lake basin. In April, two transport paths emerged: one aligned closely with the January transport path but with the location shifted slightly northward by 1° of latitude and another driven by the weak subtropical high over the southwestern Pacific, bringing moist air from the western Pacific via the South China Sea and Indochinese Peninsula. In June, the vapor sourced from the northern branch of the southern Indian Ocean subtropical high crossed the Equator and transported through various waterbodies to southwestern China, finally reaching the basin. October saw a water vapor transport path from the western Pacific, crossing the South China Sea and entering the Dongting Lake basin, influenced by the East Asian monsoon system. In different seasons, the variations in water stable isotopes along water vapor transport paths show some agreement with Rayleigh fractionation and water balance principles, as reflected in the model simulations and observations. These findings highlight the impact of atmospheric circulation on precipitation and isotopes, providing a framework for understanding water vapor isotope mechanisms and reconstructing past atmospheric conditions. This research explored how water vapor transports influenced the precipitation isotopes in the Dongting Lake basin in representative months of different seasons. By tracking water vapor from its source regions, we revealed the influence of large-scale atmospheric circulation on the transportation of water vapor to the Dongting Lake basin. The changes in water stable isotopes along the water vapor transport paths highlighted the isotopic fractionation and water vapor exchange that occurred along these paths, while the isotopic changes in the precipitation reflect the cumulative influences of water vapor transport on the local precipitation. These comprehensive insights have clarified the influences of atmospheric circulation on water vapor transport and precipitation isotopes and are thus essential for predicting regional precipitation patterns.